An Analysis of a Complementary Facet of Integrated Marketing Communications (IMC) Tool – Sales Promotion: The Significance of Sophisticated Sales Promotions in the Indian Market (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A supplemental facade impending amongst salespersons is the sales promotion as the integrated Marketing Communications (IMC) tool which endeavors to warrant the dependability of the communication and the congruent usage of mass media. In keeping with the novel requirement of the present-day epoch as the acquaintance concerning the connotation amid promotional tools and buyers, aids in enclosing the marketing approaches to entice latent shoppers and altering them into dynamic buyers which would be the lead to sophisticated sales promotions are very significant these times to stimulate Indian consumers behavior. A big percentage of budgets is expended on sales promotion by a large number of companies, these days.